The U.S. cable televisions' framing of mass shooting: a grounded discovery of competing narratives - Emelu, Maurice N. (Frontiers in Communication, 2023)
This study uses the Analysis of Topic Model Networks (ANTMA) frame analysis grounded approach and examines the 2017 Sutherland Springs, Texas mass shooting in a house of worship coverage by three U.S. cable television networks—CNN, Fox News, and MSNBC. News reports for the first seven days following the shooting were collected from the cable networks’ Twitter, YouTube, and website accounts. 290 news reports were analyzed and 760 aggregate units for frames were coded. The results support research about the news media’s emphasis on community, individual (shooter), and victims frames in cases of mass shooting. They identify differences in the issue-based frame of gun versus mental health debates. Additional new frames of empathy, interventions, incident, reactions, and security were discovered. Results also show differences in frames used and their frequency between the digital platforms of Twitter, YouTube, and websites, and between the cable organizations. These differences show each media network’s ideological perspectives or competing news narratives. The findings raise relevant questions to news coverage, policy debates about mental health and gun violence, and cultural awareness of the problem of mass shooting and public safety as the world becomes more global.